Abnormally high thermal conductivity in fivefold twinned diamond nanowires. (July 2022) - Liang, T.; Xu, K.; Han, M.; Yao, Y.; Zhang, Z.; Zeng, X.; Xu, J.; Wu, J.
Abstract: Fivefold twins (5FTs), discovered nearly 200 years ago, are a common multiply twinned structure that usually dramatically deteriorate the thermal transport properties of nanomaterials. Here, we report the anomalous thermal conductivity ( κ ) in a novel fivefold twinned diamond nanowires (5FT-DNWs). The κ of 5FT-DNWs is effectively enhanced by the defects of 5FT boundaries, and non-monotonically changes with the cross-sectional area ( S ). Above the critical S = 7.1 nm 2, 5FT-DNWs shows a constant value of κ, whereas below it, there appears a sharp increase in κ with decreasing S . More importantly, 5FT-DNWs with minimal S show a superior κ over the bulk diamond. By confirming the Normal-process-dominated scattering event, it is demonstrated that the phonon hydrodynamic behavior plays a determinative role in abnormally high κ of 5FT-DNWs with small S. The super-transported phonon hydrodynamic phenomenon unveiled in the twinned diamond nanowires may provide a new route for pursuing highly thermally conductive nanomaterials. Graphical abstract: Image 1 Highlights: The κ of 5FT-DNWs is effectively enhanced by the defects of 5FT boundaries, and can be superior over that of the bulk diamond (with remarkably high κ ) at a very small S. The phonon hydrodynamic behavior plays a determinative role in abnormally high κ for 5FT-DNWs. The super-transported phonon hydrodynamic phenomena unveiled in the twinned diamond nanowires may provide a broader scope for pursuing highly thermally conductive nanomaterials.